LINC-29. IMPACT OF RELA FUSION ON OUTCOMES OF CHILDHOOD SUPRATENTORIAL EPENDYMOMAS (ST-EPEN). (4th December 2020) - Chinnaswamy, Girish; Ramanathan, Subramaniam; Prasad, Maya; Vora, Tushar; Sahay, Ayushi; Gurav, Mamta; Sahu, Arpita; Moiyadi, Aliasgar; Shetty, Prakash; Goda, Jayant Sastri; Krishnatry, Rahul; Gupta, Tejpal; et al.
Abstract: BACKGROUND: Ependymomas are heterogenous group of tumours with variable clinical course and diverse molecular features. RELA fusion status has been reported to have prognostic impact in ST-EPEN. Our retrospective study analysed the prevalence and clinical impact of RELA fusion in childhood ST-EPEN at our centre. STUDY METHODS: FFPE tissues of all childhood ST-EPEN diagnosed during 2011–2017 were evaluated for RELA fusion 1/2 by RT-PCR. Children were treated as per guidelines by the Neuro-oncology multidisciplinary team. Outcomes were correlated with RELA fusion, histological features and immunohistochemical parameters(L1CAM expression and Mib-1 index). Only patients with therapy details were included. RESULTS: A total of 37 patients(0–50 years) with ST-EPEN were included(median age-10.2 years; boy:girl ratio-1.4:1)for analysis. Histological grade II, II/III and III was seen in 4(11%), 2(5%) and 31(84%) patients respectively. Mib-1 index was assessable in 33 patients of which, 9 patients (24%) had a Mib-1 index >20%. RELA fusion was detected in 13(35%)tumors. The 3-year and 5-year EFS/OS of the overall cohort was 64.2%/83.6% and 60.1%/73.1% respectively. The 3-year/5-year EFS of RELA-positive tumors was inferior compared to RELA-negative tumours (53.8%/36% v/s 62.6%/53.6%; p=0.391). The 3-year/5-year EFS of tumors expressing L1CAM versus negative-expression was comparable (61.1%/55%v/s59.8%/47.9%;p=0.44). Presence of Mib-1>20% correlated with inferior survival (5-year EFS:81.1%vs22.2%; p<0.01). CONCLUSIONS: ST-EPEN with RELA fusion had trend towards increased relapse/progression. High Mib-1 correlated with poor survival. RELA fusion status needs to be studied in a larger cohort prospectively to confirm its clinical impact.